Enhancing Legal Education Through Case-based E-consultation: An Empirical Study Of The Faculty Of Shariah And Law Legal Clinic At Usim - Nabihah Khairulazhar; Nur Najla Mohamad Asri; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
In contemporary society, the Muslim community often encounters complex challenges that require resolution within the framework of the Syariah legal system. This scenario presents an invaluable opportunity for law students to engage directly with community needs through practical learning experiences. This study explores enhancing legal education by implementing case-based e-consultation at the Legal Clinic of the Faculty of Shariah and Law (FSU), Universiti Sains Islam Malaysia (USIM). The primary objective is to analyse and systematise real case data from e-consultation sessions into structured learning resources for academic use. Employing document analysis, the study scrutinises materials related to the e-consultation process, providing critical insights into its practical deployment. Despite positive outcomes, challenges such as technical constraints, inconsistent case documentation, and suboptimal pedagogical structuring were observed. To address these issues, the study advocates for developing a comprehensive case database and ongoing training for faculty to support effective implementation. Ultimately, the findings endorse the integration of e-consultation as a sustainable, experiential, and community-oriented pedagogical tool, contributing significantly to advancing legal education curricula.